Material didáctico virtual para el fortalecimiento de la escritura académica en español como segunda lengua en comunidades indígenas (2021)
The purpose of this work is to strengthen academic writing in Spanish as second language of indigenous communities that are part of training programs professional in Colombia, this is how the current report presents the main needs, theoretical postulates and other processes that made possible the construction of a Virtual teaching material hosted on a web page. This material is divided into three thematic units that seek to strengthen written production processes based on textual properties such as coherence, cohesion and a last section focused on variables linguistics. For this reason, each of the units proposed is recognized as a means by the one that each student can strengthen their textual production, once studying in some higher education program.